THE EFFECTIVENESS OF THE HUMANISTIC APPROACH TO CHARACTER EDUCATION IN THE INDEPENDENT CURRICULUM ERA - Yusuf, Achmad (PT. Hafasy Dwi Nawasena, 2025)
Character education is an important pillar in the implementation of the Independent Curriculum to shape students with integrity, responsibility, and high empathy. One approach considered in line with this spirit is the humanistic approach, which positions students as active subjects in the learning process. This study aims to test the effectiveness of the humanistic approach in improving five indicators of student character: empathy, responsibility, independence, honesty, and cooperation. The research method used was quantitative with a quasi-experimental design of the non-equivalent control group design, involving 60 junior high school students from two different schools. Data analysis techniques used an independent t-test and effect size calculation. The results showed that the group learning with the humanistic approach experienced significant character improvement compared to the control group, with a significance value of p = 0.000 and an effect size of 1.52. The discussion shows that the humanistic approach is effective in creating a reflective, empathetic learning climate and encouraging the internalization of values. The conclusion of this study states that the humanistic approach is an appropriate strategy in strengthening character education, in line with the objectives of the Independent Curriculum.